2021
DOI: 10.1177/0269881120986422
|View full text |Cite
|
Sign up to set email alerts
|

Hallucinogenic/psychedelic 5HT2A receptor agonists as rapid antidepressant therapeutics: Evidence and mechanisms of action

Abstract: Major depressive disorder (MDD) is among the most prevalent mental health disorders worldwide, and it is associated with a reduced quality of life and enormous costs to health care systems. Available drug treatments show low-to-moderate response in most patients, with almost a third of patients being non-responders (treatment-resistant). Furthermore, most currently available medications need several weeks to achieve therapeutic effects, and the long-term use of these drugs is often associated with significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 64 publications
(131 reference statements)
1
38
0
1
Order By: Relevance
“…Since the early 20th century, there has been considerable interest in using psychedelics to treat mental illnesses (Carhart-Harris and Goodwin, 2017 ; Bogenschutz and Ross, 2018 ; Nichols and Walter, 2021 ). Numerous clinical studies have shown encouraging therapeutic potentials of psychedelics, particularly LSD and psilocybin, and to a lesser extent ayahuasca, ibogaine, and dipropyltryptamine (DPT), in treating disorders including addiction to alcohol, nicotine, or illicit drugs, anorexia nervosa, depression, distress and anxiety concerning death, obsessive-compulsive disorder, and post-traumatic stress disorder (Bogenschutz and Johnson, 2016 ; Johnson et al, 2019 ; Dos Santos and Hallak, 2020 ; Foldi et al, 2020 ; Krediet et al, 2020 ; Andersen et al, 2021 ; Dos Santos et al, 2021 ). The neuroplastic effects of psychedelics, however, have only been appreciated much more recently.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Since the early 20th century, there has been considerable interest in using psychedelics to treat mental illnesses (Carhart-Harris and Goodwin, 2017 ; Bogenschutz and Ross, 2018 ; Nichols and Walter, 2021 ). Numerous clinical studies have shown encouraging therapeutic potentials of psychedelics, particularly LSD and psilocybin, and to a lesser extent ayahuasca, ibogaine, and dipropyltryptamine (DPT), in treating disorders including addiction to alcohol, nicotine, or illicit drugs, anorexia nervosa, depression, distress and anxiety concerning death, obsessive-compulsive disorder, and post-traumatic stress disorder (Bogenschutz and Johnson, 2016 ; Johnson et al, 2019 ; Dos Santos and Hallak, 2020 ; Foldi et al, 2020 ; Krediet et al, 2020 ; Andersen et al, 2021 ; Dos Santos et al, 2021 ). The neuroplastic effects of psychedelics, however, have only been appreciated much more recently.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In animal studies, 5HT2a receptor agonists enhanced the cognitive flexibility and response inhibition of individuals [7]. In addition, this mechanism has been associated with antidepressant-like effects in animal models [8]. Intravenous administration of psilocybin significantly decreases the positive coupling of the medial prefrontal cortex and the posterior cingulate cortex, and these brain regions are known to be involved in patients with depression.…”
Section: Introductionmentioning
confidence: 97%
“…Indeed, there is now considerable interest in exploring the psychotherapeutic potential of hallucinogens, with 13 trials of psilocybin ( 2 ) undertaken in 2020 alone [ 5 ]. The renewed exploration of hallucinogens in a therapeutic setting raises important ethical and scientific consideration, and highlights the need for basic research on the action of hallucinogens in human brain [ 6 , 7 ]. The only recent review on imaging of hallucinogen actions focusses mainly on the fMRI literature [ 8 ].…”
Section: Introductionmentioning
confidence: 99%